Case report: Ruxolitinib as first-line therapy for secondary hemophagocytic lymphohistiocytosis in patients with AIDS - Liu, Xiang; Zhu, Xueling; Zhou, Xiaotang; Xie, Yirui; Xiang, Dairong; Wan, Zhikai; Huang, Ying; Zhu, Biao (Frontiers in Immunology, 2022)
Background Hemophagocytic lymphohistiocytosis (HLH) is a fatal immunological syndrome resulting from excessive production of inflammatory cytokines. The conventional therapies for HLH, which are based on cytotoxic agents, are not always efficacious and safe, especially in patients with severe immunodeficiency. Ruxolitinib, a strong inhibitor of Janus kinase (JAK) 1/2, has already been evaluated as salvage and first-line therapy for HLH. Despite its promising efficacy and tolerability in the treatment of secondary HLH, the efficacy and safety of ruxolitinib in HLH patients with HIV infection remain to be investigated. Case presentation Two men (ages: 45 and 58 years) both presented at our hospital with a high fever. They were found to be HIV-positive with severe immunodeficiency and opportunistic infections. Their laboratory tests showed severe pancytopenia, hypofibrinogenemia, hypertriglyceridemia, and increased levels of inflammatory factors and ferritin. Hemophagocytosis was found in the bone marrow, and abdominal computed tomography or ultrasonography showed splenomegaly. Both patients were diagnosed with infection-induced HLH due to severe immunodeficiency. Given they were both highly immunocompromised, we chose ruxolitinib as a first-line treatment alternative to cytotoxic chemotherapy. Rapid remission of clinical symptoms and normalization of laboratory parameters were achieved after ruxolitinib therapy. Neither patient had any associated adverse drug reactions or other laboratory abnormalities. Both patients were eventually discharged and ruxolitinib was discontinued as their disease alleviated, and they did not show signs of relapse during the 3- and 5-month of follow-up examinations. Conclusion We described two cases of AIDS-related secondary HLH treated with ruxolitinib. Our cases highlight the feasibility of using ruxolitinib as a first-line therapy in patients with HIV infection and secondary HLH. Nevertheless, the safety and efficacy of this novel treatment need to be evaluated in large clinical trials in the future.